ANALISIS KARTU ACCESS CONTROL PINTU MENGGUNAKAN METODE USER ACCEPTANCE TEST PADA MUSEUM BANK INDONESIA - Mohamad Miftahhul Khaer; Nur Nawaningtyas Pusparini (STMIK Widuri Jakarta, 2023)
Safety in the environment, whether at home, at work or in the open, is the hope that everyone wants in all their activities in public places. Security guarantees are also really needed in several business areas and workplaces to avoid interference from any party. In entrance access control, access control alludes to the act of restricting access to an office to approved persons only. When entering a room through an entrance that requires a manual key there are many restrictions. The aim is to find out the advantages or disadvantages of access control devices so that we can anticipate that the devices will not be easily damaged, and to find out the results of testing the level of acceptance of access control devices so as to prevent misuse of access cards. The method used is User Acceptance Test (UAT). The result is that based on the results of a questionnaire that has been carried out at the Bank Indonesia Museum, it is known that testing using UAT can help in knowing the advantages and disadvantages of access control devices so that they can anticipate that the devices will not be easily damaged. In this case, it was found that 27 respondents answered agree and 23 respondents answered strongly agree, stating that users felt that smart cards often did not function when they wanted to access the work space in the Bank Indonesia museum, and the level of acceptance of access control devices was 81% based on the assessment criteria above, namely very good, so it can prevent misuse of access cards at the Bank Indonesia Museum.